THE IMPACT OF CULTURAL IMPERATIVES ON ACADEMIC WRITING IN ARAB CONTEXTS - Al-Asadi, Sami (European Scientific Journal, ESJ, 2015)
EFL Arab students have experienced difficulties in replicating the cultural thought patterns of L1 English users (Kaplan, 1966; Hirose, 2003). Also, they experience difficulties in replicating the textual expectations of academic genre in the English-speaking discourse community (Al- Khuweileh &Al-Shoumali, 2000; Al-Hazmi & Schofield, 2007) at the tertiary level. However, two factors diminish their ability to produce an effective and efficient written product in academia. To this end, the purpose of this study is to answer the following question “Can a modified integrated process-genre model (MIM) extend and enrich the repertoire of Iraqi undergraduates’ writing competence to encounter the challenges of academic writing?” Third-year EFL students English majors were the targeted research population. The participants of this study were 92 students. They were randomly assigned to two relatively comparable groups. These groups include the non-intervention being taught by the current product-based approach, and the intervention being taught by the MIM. All the participants were pre-tested for their proficiency in academic argumentative writing before the commencement of the intervention. Following the treatment, a post-test was administered to them. A mixed methods research methodology was adopted. An Exploratory Sequential Mixed Methods Research Design (Creswell & Plano Clark, 2007) was employed to analyse the data coming from the students’ pre-and posttest’s written essays. The pre-test results had the evidence to suggest that the two groups were relatively similar and there were no statistically significant differences in their performance. The finding showed that most of the intervention group students achieved improvements in the quality of their argumentation as compared to peers in the non-intervention group.